Archetypes of sourcing decision-making: The influence of contextual factors on consensus, argumentation and cabal. Issue 2 (19th December 2019) - Schleper, Martin C.; Blome, Constantin; Stanczyk, Alina
Abstract : Purpose: The purpose of this paper is to develop taxonomy of sourcing decision-making (SDM) archetypes and explore how different contextual factors influence these archetypes when global sourcing of complex components is considered a viable option. Design/methodology/approach: A multiple case study approach with five in-depth cases is employed. In total, 19 interviews as well as publicly available and internal data from large buying firms headquartered in Austria and Germany were collected and analyzed. Findings: The results reveal three different SDM archetypes which are described in detail (i.e. "consensus, " "argumentation" and "cabal"). Furthermore, it is found that these archetypes are mainly influenced by three contextual factors: sourcing maturity, product complexity and leadership style. The final model comprises six propositions which illustrate how these contextual factors determine companies' SDM archetypes. Research limitations/implications: The study contributes to theory development at the intersection of organizational buying behavior and the (global) SDM literature. Thereby, it answers the call for more rigorous investigation of the influence of contextual factors on SDM processes. Practical implications: The findings enable practitioners to better understand and consequently manage SDM processes and their outcomes. By supporting decision-makers in identifying SDM archetypes, this study allows sourcing managers and teams to make better decisions by avoiding problems that occur in situations in which the preferred decision-making type would result in suboptimal decisions. Originality/value: The study provides a first step toward taxonomy of SDM archetypes and is among the first that explores their underlying contextual factors.